Factors affecting the choice of construction project delivery in developing oil and gas economies. (3rd May 2016) - Martin, Hector; Lewis, Timothy M.; Petersen, Andrew
ABSTRACT: Construction academics and practitioners often disagree on which set of factors should take precedence over another and the basis for their inclusion in selecting a project delivery method. This disagreement exacerbates the probability of project failure, which could be detrimental to developing economies. Despite significant cost overruns and these economies being the largest contributors towards global energy sector growth, there is limited knowledge on appropriate factors to be used for selecting project delivery methods in developing oil and gas nations. An evaluation undertaken in Trinidad reveals there are no significant differences in the mean expressed by 133 professionals in relation to 48 variables obtained from the literature on project delivery selection. However, there were several differences in the respondents' views, based on their roles as client, contractor, or consultant. Using principal component analysis, all 48 variables were reduced to 11 factors, which were confirmed using split sample verification. These 11 factors accounted for 67% of the total variance of the solution. The top six factors are: Owners' Control Over the Design; Project Type and Client Familiarity; Finance and Payment Method; Project Scale in terms of Scope and Cost; Contract and Risk; and Time Constraints. Although existing selection approaches do not emphasize the inextricable link between contract and the selection of project delivery methods, this link which is evident in practice is reinforced by the factors provided. How these factors are different and how these differences facilitate efficient project execution between public and private sector procurement is presented in this article.